(3MGTjI CHjQhOj Ydi MGTjI GdSjO Ydi TQM GdbWH Ydi GdTSjIs - (3GdCHjQhOj, CHj GdMSf OGfTefOs ((3CQehj (B( (3COehj (B) - (3eOQjI GdWGeQjIs)
(3ChdgG (B:s
(3GdMeO ddg GdPj fhQ bdhH GdYGQajf HCfhGY CfhGQ GdeYGQa GdEdgjI (B... (3eYdbG CjGeG Ydi eG fSH Edi SdWGf GdeMbbjf GdeQJVi GdTQja bOS SQg ef GdMhGTj GdeJYdbI HTQM GdQSGdI GdTeSjI bhdg hQJHJg Cj QJHJ GdcJGH hhVYJ (B...s
(3BNQgG (B:s
... (3acja HUOb fbjVg CYfj dG TjA ef GdQhej HCHjV HGdEecGf hCjVG dh UOa gPG GdUOb bhdfG dG TjA ef GdQhej HQhej HGdEecGf dCf GdQhejI HGYJHGQ hVa GdHjGV eG OGe UGQ SHg Yf Gdhej HGdEecGf MGQ SdHgG CjVG cPdc JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B2\1063s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdadSaI hGdefWbs